Exciton control enables high-performance colloidal quantum well light-emitting diodes - Hu, Sujuan (2024)
Two-dimensional (2D) nanocrystals are promising for optoelectronic and microelectronic technologies. However, the performance of 2D nanocrystal light-emitting diodes (LEDs) remains limited. Here, exciton dynamics are rationally controlled by both shell engineering and device engineering, obtaining colloidal quantum well LEDs (CQW-LEDs) with superior performance. The formation of CQW films on charge transport layers shows an excellent photoluminescence quantum yield of 76.63%. An unreported relationship among Auger lifetime, electron confinement energy, and external quantum efficiency (EQE) in 2D nanocrystal devices is directly observed. The optimized CQW-LEDs possess a maximum power efficiency of 6.04 lm W−1 and a current efficiency of 9.20 cd A−1, setting record efficiencies for 2D nanocrystal red LEDs. Additionally, a remarkable EQE of 13.43% has been achieved, accompanied by an exceptionally low efficiency roll-off. Significantly, EQE for flexible CQW-LEDs is 42-fold higher than the previous best results. Furthermore, active-matrix CQW-LEDs on printed circuit boards are developed. The findings not only unlock new possibilities for controlling exciton dynamics but also provide an alternative strategy to achieve high-performance 2D nanocrystal based applications.